1997
DOI: 10.1111/j.1945-5100.1997.tb01301.x
|View full text |Cite
|
Sign up to set email alerts
|

Equilibrated ordinary chondrites: Constraints for thermal history from iron‐magnesium ordering in orthopyroxene

Abstract: Abstract-Iron-magnesium ordering was determined in orthopyroxenes from two suites of unshocked (shock stage S 1, S2), equilibrated L-and LL-chondrites (10 grains from 5 meteorites and 7 grains from 4 meteorites, respectively) by means of single crystal x-ray diffraction (SCXRD). This study, together with a previous investigation of H-chondrites (1 3 grains from 8 meteorites), produces an internally consistent data set about the thermal record in equilibrated ordinary chondrites (EOCs).The major feature outline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 22 publications
1
8
0
Order By: Relevance
“…rates of equilibrated H chondrites near their closure temperature T c (450-550 °C) is in all cases very fast compared to Trieloff et al (2003), and is independent of the petrologic type, as observed by Folco et al (1997). The observed cooling rate at around 520 °C of Trenzano could indicate fast cooling after shock-reheating, or cooling in a shallow environment, possibly caused by denudation as a consequence of excavation of formerly overlying rocks or by fragmentation of the parent body into sizable blocks.…”
Section: Thermal Historysupporting
confidence: 57%
See 2 more Smart Citations
“…rates of equilibrated H chondrites near their closure temperature T c (450-550 °C) is in all cases very fast compared to Trieloff et al (2003), and is independent of the petrologic type, as observed by Folco et al (1997). The observed cooling rate at around 520 °C of Trenzano could indicate fast cooling after shock-reheating, or cooling in a shallow environment, possibly caused by denudation as a consequence of excavation of formerly overlying rocks or by fragmentation of the parent body into sizable blocks.…”
Section: Thermal Historysupporting
confidence: 57%
“…Shock heating and annealing may obscure pre-shock thermal history and, depending on the highest temperature reached during shock, may selectively disorder specific mineral closing temperatures. However, Trenzano is an S2 chondrite, and such weakly shocked meteorites are not expected to have undergone significant reheating due to shock (Folco et al 1997). According to Rubin (2004), all ordinary chondrites reached shock stage S3-S6 due to collisional events and then underwent post-shock annealing, which not only obliterated most of their primary shock features but also contributed significantly to the final thermometamorphism displayed.…”
Section: Thermal Historymentioning
confidence: 99%
See 1 more Smart Citation
“…Evaluation of cooling rates of chondrites based on precise U-Pb dating of pyroxene and phosphates has several differences from the methods of determination of cooling rates based on metallography, 244 Pu fission tracks, and Fe-Mg ordering in orthopyroxene (Wood, 1979;Lipschutz et al, 1989;Folco et al, 1997). First and most important, the cooling rate values are precisely linked to the absolute time scale.…”
Section: Closure Temperatures For Pb Diffusion and Significance Of Agesmentioning
confidence: 97%
“…The cooling rates determined by the metallographic technique, which are mostly 1-10 3 C Ma -1 in the temperature range of 400-500 C, are compatible with cooling rates in the range 100-500 C determined by the fission track technique. A third technique based on Fe-Mg ordering in orthopyroxene gives cooling rates in the range 340-480 C that are systematically higher by several orders of magnitude (Folco et al, 1997), probably because metamorphism was insufficient to reequilibrate the ordering imposed during chondrule formation (Artioli and Davoli, 1994). Cooling rates can also be estimated from radiometric age data for mineral grains that close isotopically at different temperatures Bogard, 1995Bogard, , 2011Ganguly and Tirone, 2001).…”
Section: Thermal History and Modelingmentioning
confidence: 99%